(untitled) (Czech Journal of International Relations, 1966)
The study was written in connection with the gathering of material, research, and preparation for larger work. Its objective is to sum up the given problems. By way of introduction, it mentions the principal centers of research and teaching of international relations in the United States, important magazines and textbooks as well as more extensive theoretical works and reviews. It emphasizes the quantitative expansion that has been achieved in the sphere.